Spatial Congruence or Mismatch Between Phylogenetic and Functional Structure of Seed Plants Along a Tropical Elevational Gradient: Different Traits Have Different Patterns - Zhou, Yadong; Wang, Shengwei; Njogu, Antony W.; Ochola, Anne C.; Boru, Biyansa H.; Mwachala, Geoffrey; Hu, Guangwan; Wang, Qingfeng (Frontiers in Ecology and Evolution, 2019)
Compared to species richness, few studies have investigated the patterns and relationship of phylogenetic and functional structures along elevational gradients. Here, we used the general additive models to determine the trends of taxonomic diversity (species richness, SR), phylogenetic and functional diversity (PD and FD), phylogenetic structure net relatedness index (NRI), and functional structure net functional relatedness index (NFRI) of seed plants along the elevational gradient in Mount Kenya, a tropical mountain in Africa. We measured growth form, fruit type, maximum height, and maximum leaf size of each species, calculated the phylogenetic signal of each trait, and tested the Pearson correlation coefficients between NRI and NFRI of each trait. Our results showed that SR, PD, and FD decreased gradually along the elevational gradient. NRI exhibited a fluctuating pattern along the elevational gradient, while NFRI of the four functional traits showed noticeably different patterns. We concluded that the relationship between the phylogenetic and functional structures in different functional traits could be congruent or mismatched along the elevational gradient. Compared with relatively conservative categorical traits (e.g., growth form and fruit type), continuous traits (e.g., height and leaf size) have a random or convergent evolutionary pattern. Therefore, they could be more easily affected by the environment and possibly have higher phenotypic plasticity.